2014
DOI: 10.1038/cddis.2014.98
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming inherent resistance to histone deacetylase inhibitors in multiple myeloma cells by targeting pathways integral to the actin cytoskeleton

Abstract: Histone deacetylase inhibitors (HDACi) are novel chemotherapeutics undergoing evaluation in clinical trials for the potential treatment of patients with multiple myeloma (MM). Although HDACi have demonstrable synergy when combined with proteasome inhibitors (PIs), recent evidence indicates that combination of HDACi and PI is beneficial only in a subset of patients with advanced MM, clearly indicating that other rational combinations should be explored. In this context we hypothesized that understanding the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Previous reports have suggested that various mechanisms such as increased drug efflux, target overexpression and/or desensitization, chromatin/epigenetic alterations, increased antioxidant expression, and the activation of prosurvival signaling underlie HDAC inhibitor resistance [25]. Recently, constitutive activation of STAT proteins has been reported to predict vorinostat resistance [32], and targeting signaling pathways associated with the actin cytoskeleton has been reported to rescue multiple myeloma cells from HDAC inhibitor resistance [33]. In addition, a recent study identified 9 genes associated with the response of HDAC inhibitors in NSCLC cells; of these, NQO1, SEC23A, and PSME2 were closely associated with drug activity [20].…”
Section: Discussionmentioning
confidence: 97%
“…Previous reports have suggested that various mechanisms such as increased drug efflux, target overexpression and/or desensitization, chromatin/epigenetic alterations, increased antioxidant expression, and the activation of prosurvival signaling underlie HDAC inhibitor resistance [25]. Recently, constitutive activation of STAT proteins has been reported to predict vorinostat resistance [32], and targeting signaling pathways associated with the actin cytoskeleton has been reported to rescue multiple myeloma cells from HDAC inhibitor resistance [33]. In addition, a recent study identified 9 genes associated with the response of HDAC inhibitors in NSCLC cells; of these, NQO1, SEC23A, and PSME2 were closely associated with drug activity [20].…”
Section: Discussionmentioning
confidence: 97%
“…These changes undoubtedly will cause cancer cells undue stress, and it may be that FAK is a key component of the pathways that mitigate that stress and permit cancer cell survival. In this regard, we note that cell shape (the regulation of which FAK contributes to via well-recognized effects on actin and adhesion networks) can alter histone acetylation (26) and that gene expression profiling of HDAC inhibitor resistance in human myeloma cell lines is reported to involve actin cytoskeleton-associated genes, and FAK itself, as part of a resistance gene signature (27). This supports the link that we have identified here between the regulation of the cellular epigenetic state by HDAC activity and FAK signaling, revealing a co-dependency in multiple cancer cell lines.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies indicated that inherent resistance of HDACi was commonly observed in clinical trials of breast cancer patients. 4448 However, the mechanism of HDACi resistance in breast cancer is still unclear. Based on the findings from our work, we speculate that enhanced HDAC5 expression in response to treatment with conventional HDACi could contribute to refractoriness to HDACi therapy.…”
Section: Discussionmentioning
confidence: 99%